Maternal and foetal risks associated with teenage pregnancy - a comparative retrospective study in Turkey - Mehmet Nuri Duran; Eren Pek; Süreyya Sarıdaş Demir; Kübra Özkan Karacaer; Bülent Demir (Taylor & Francis Group, 2024)
Background Adolescent pregnancy is defined as pregnancy occurring in young women between the ages of 10 and 19 years. Adolescent pregnancies, which are among the social healthcare concerns in developed and developing countries, have negative effects on maternal and infant health. Pregnancy in adolescence puts the health of both the mother and child at risk, as adolescent pregnancies have higher rates of eclampsia, systemic infection, low birth weight, and preterm delivery compared to other pregnancies. In this study, the effects of education level, smoking, and marital status on maternal and foetal outcomes in adolescent pregnancies were evaluated.Methods The records of a total of 960 pregnant women (480 pregnant adolescents aged 15-19 years and 480 pregnant adult women aged 20-26 years) were examined retrospectively. The demographic data of the groups and maternal and foetal outcomes of the pregnancies were compared. A logistic regression model was established as a statistical method for reducing confounding effects.Results Unmarried women were statistically significantly more prevalent in the adolescent group (38.3% vs. 7.3%). Among the considered risk factors, preeclampsia (2.9% vs. 0.8%) and smoking (29.8% vs. 9.8%) were statistically significantly more common in the adolescent group. When the groups were compared in terms of risk factors in pregnancy, it was found that pregnancy in adolescence was associated with a 3.04-fold higher risk of smoking, 5.25-fold higher risk of being unmarried, 3.50-fold higher risk of preeclampsia, and 1.70-fold higher risk of intrauterine growth retardation (IUGR).Conclusions This study demonstrates an increased risk of preeclampsia, IUGR, and smoking during pregnancy in adolescent pregnant women. These findings can be used to identify adolescent pregnancies requiring specific assistance and to take measures to reduce the probability of adverse outcomes.